Root rot biocontrol for indoor poinsettia with Trichoderma spp. - Osuna-Canizalez, Felipe de Jesús; Moreno-López, María Félix; García-Pérez, Faustino; Ramírez-Rojas, Sergio; Canul-Ku, Jaime (Revista Mexicana de Ciencias Agrícolas, 2018)
In Morelos, root rot caused by Fusarium spp., is one of the main diseases of indoor poinsettia. In order to prevent or control its devastating effect, frequent applications of chemical products are performed, with inherent risks to human health and environment. In quest for alternative biorational options, an essay in which three commercial strains of Trichoderma spp., was done, in three different substrates: S1= “organic soil” (70% v/v)+thick tezontle (15% v/v)+thin tezontle (10% v/v)+agrolita (5% v/v); S2= peat moss (80% v/v)+ coconut fiber (20% v/v); S3= “organic soil” (70%)+“tepojal” (30%), in most common commercial varieties, Freedom Red and Prestige Red. A factorial design of 4 x 3 x 2 treatment was used and resulting treatments were evaluated in a completely random design with six repetitions. Regards root rot incidence, commercial strains of Trichoderma spp., did not show differences between them, either with chemical control. Root rot was associated with S2, due low aeration capacity, and only it was seen in Prestige Red. Population of Trichoderma spp.,(UFC g-1) in the substrate at end of cycle was the same (p≤ 0.05) between commercial strains and between them and the control (without inoculation), due presence of native strains of Trichoderma in organic components of substrates (“organic soil”, peat moss and coconut fiber).
Keywords: Euphorbia pulcherrima; Fusarium spp.; native strains; substrates; varieties